2021
DOI: 10.1002/anie.202015669
|View full text |Cite
|
Sign up to set email alerts
|

Probing Physical Oxidation State by Resonant X‐ray Emission Spectroscopy: Applications to Iron Model Complexes and Nitrogenase

Abstract: The ability of resonant X-ray emission spectroscopy (XES) to recover physical oxidation state information, which may often be ambiguous in conventional X-ray spectroscopy, is demonstrated. By combining Kb XES with resonant excitation in the XAS pre-edge region, resonant Kb XES (or 1s3p RXES) data are obtained, which probe the 3d n+1 final-state configuration. Comparison of the non-resonant and resonant XES for as eries of high-spin ferrous and ferric complexes shows that oxidation state assignments that were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 80 publications
0
51
0
Order By: Relevance
“…We have synthesized and structurally characterized (Fig. 2 ) a series of [L 2 Fe 2 Q 2 ] − dimers (with tetrahydrofuran (THF)-solvated K + counter ions) supported by a β-diketiminate ligand (L − ), where the bridging µ-Q 2– ligands are S 2– ( 1 ) 27 , Se 2– ( 2 ) and Te 2– ( 3 ). To the best of our knowledge, compound 3 is the first reported synthesis of an [Fe 2 Te 2 ] + complex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have synthesized and structurally characterized (Fig. 2 ) a series of [L 2 Fe 2 Q 2 ] − dimers (with tetrahydrofuran (THF)-solvated K + counter ions) supported by a β-diketiminate ligand (L − ), where the bridging µ-Q 2– ligands are S 2– ( 1 ) 27 , Se 2– ( 2 ) and Te 2– ( 3 ). To the best of our knowledge, compound 3 is the first reported synthesis of an [Fe 2 Te 2 ] + complex.…”
Section: Resultsmentioning
confidence: 99%
“…57 Fe metal was purchased from EurIsotop (Cambridge Isotope Laboratories) and used as received. SePMe 3 , TePCy 3 (Cy = cyclohexyl), LH, 57 FeCl 2 , LFe(PhMe), L 2 Fe 2 S 2 ( 1 ox ) and [K(THF) 6 ][L 2 Fe 2 S 2 ]·2THF ( 1 ) were prepared as previously reported 27 , 46 50 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 56 , 57 Furthermore, we have demonstrated that Se Kβ HERFD XAS exhibits spectral resolution matching Se Kα HERFD XAS, and thus a single experimental setup allows access to complementary Se VtC XES and HERFD XAS measurements. Future studies will explore resonant measurements as a means of enhancing sensitivity to changes in Se chemical and electronic structure—analogous to recent Fe resonant X-ray emission spectroscopic studies 58 —as well as the feasibility of laboratory-based Se X-ray emission measurements.…”
Section: Discussionmentioning
confidence: 99%